Fatigue Analysis on Hybrid Sugar Palm-Kenaf Fibre Reinforced Polypropylene Composites - Bachtiar, Dandi; Siregar, Januar Parlaungan; Zulfadhli; Masri; Arhami; Siregar, Ramdhan Halid; Jalil, Saifuddin Muhammad (Journal of Engineering and Science, 2024)
ABSTRACT Hybrid natural-natural fibre reinforced polymer composites become attractive alternative to seek the friendly-environmentally materials. Study on the durability level of the hybrid composites have the importance reason due to the role in application as structural function. This study focuses on examining the fatigue strength of polypropylene polymer composites reinforced with hybrid sugar palm-kenaf fibres. The hybrid composite materials were prepared by mixing the fibres and matrix with several compositions. There are five composition types of specimens that evaluated, such as 70:10:10, 70:15:15, 70:20:10, 80:10:10 and 90:5:5. The hybrid composites were composed by PP, sugar palm fibre and kenaf fibre. Furtheremore the tensile test were conducted to find the value of ultimate tensile strength for every specimens of hybrid composites. The fatigue test also were conducted with four level of stress i.e. 80%, 70%, 60% and 50%. The results show that in the lower level of stress, the hybrid composites with higher content of sugar palm fibre posses the better performance of fatigue life compare to the others